The Meanings of the Cultural Landscape in Pantai Lido Waterfront According to Malay Oldies Perspective - Mohd Amirul Hussain , Nur Afikah Idrus , Mohd Yazid Mohd Yunos, Nor Atiah Ismail , Nor Fazamimah Mohd Ariffin , Sumarni Ismail (International Journal of Advanced Science and Technology, 2020)
Many researchers consider the definition of ‘Meaning’ as it plays an essential role, especiallyin the perspective of place image. The meaning of place is manifested through the symbolism ofplace that considered as universal as they represent the crucial tendencies of the human mind.The meaning of the place remains the precious memories that make such a memorable place as itcan enhance the identity of the place. The objective of this study is to obtain the criteria of thecultural landscape elements that exist in Pantai Lido, which creates the meaning of the place inPantai Lido waterfront according to the Malay oldies’ perspective. Furthermore, in achievingthe objective, a qualitative method was conducted which involved in-depth interviews andparticipant observation by collecting the informants’ perception, memories, attitudes and beliefsas the subjective reality manifested at both of the psychological and social-cultural levels. Thefindings demonstrate the meaning of place as the factors that make Pantai Lido more noticeableand memorable. Moreover, the elements that make the cultural landscape in Pantai Lido moreprominent is due to the local people’s place attachment and the environment that evoked itsmemories and meanings. This study will carry on by suggesting a survey on the importance ofmeanings of place and its association involvement in cultural landscape conservation. Thisindicates that perhaps the local authorities and the policymakers need to improve and reshufflethe current regulations for urban waterfront development in Malaysia